Summary of Best Evidence on the Application Timing and Management Strategies of Compression Therapy for Chronic Wounds - Peng, Qianqian; Wu, Shengmei; Wu, Xiandi; Zhang, Lili; Hu, Yanli; Yao, Bangyan; Lei, Ying (International Journal of Public Health and Medical Research, 2025)
Background: Chronic wounds, including venous ulcers and diabetic foot ulcers, impose significant clinical and economic burdens globally. Compression therapy is a cornerstone intervention, yet its optimal application timing and management strategies lack standardized guidelines. Methods: According to the ‘6S’ evidence resource model, evidence retrieval is searched from the top-down and collected relevant guidelines, best practices, evidence summaries, systematic reviews and expert consensus. The retrieval time limit was from the database establishment to 20 March 2025. Two reviewers independently screened and evaluated the literature, and then extracted and summarised the evidence according to the JBI grading of evidence and recommendation system. Results: This study summarizes 18 pieces of evidence in 7 aspects, including indications, contraindications, application, assessment, management strategies, effectiveness, and adverse reactions, related to the application timing and management strategies of compression therapy for chronic wounds. Conclusions: Compression therapy significantly enhances chronic wound healing but requires rigorous contraindication screening and dynamic pressure adjustment. Clinicians should adopt evidence-based protocols integrating ABI assessments and patient education. Future innovations should focus on smart devices and longitudinal outcome tracking.